Linguistic challenges for agricultural law comparativism - Martínez, José (Przegląd Prawa Rolnego, 2021)
Agricultural law combines two opposing directions of development of law in general. One is connected with the local or regional element and indeed, like no other discipline, is linked to a specific region, culture, tradition and linguistic specificity, being a consequence of the specific nature of agricultural law. On the other hand, at the level of the European Union it is characterised by the greatest degree of integration. The Common Agricultural Policy has made agricultural law locally and regionally rooted but, at the same time, it has created a specific technical language of European agricultural law. Therefore, conducting a comparative legal research into the field of agricultural law faces a particular challenge as it requires combining both local and regional linguistic specificities with the European technical language of agricultural law. This relativism of the technical language of agricultural law does not, however, stand in the way of legal comparativism. However, apart from the linguistic knowledge, it requires the researcher to possess thorough cultural, social and economic knowledge of another country. Professor Budzinowski, unlike many other scholars, embodies these skills in his comparative legal research.